34.1k views
5 votes
Mai and Noah also solved the equation, but some of their steps have errors. Fid the incorrect step in each solution and explain why it is incorrect.

User Cjk
by
5.0k points

2 Answers

3 votes

Answer:

what equation

Explanation:

User Sham
by
5.4k points
6 votes

The incorrect step in Mai's and Noah's solution are presented as follows;

The incorrect step in Mai's solution; 7·x + 3 = 3(9)

The incorrect step in Noah's solution; 27·x + 3 = 27

The details on why the step are incorrect can be presented as follows;

The solution to the equation 14·x - 2·x + 3 = 3·(5·x + 9) can be presented as follows;

14·x - 2·x + 3 = 3·(5·x + 9)

12·x + 3 = 15·x + 27

12·x - 15·x = 27 - 3

-3·x = 24

x = 24/(-3)

x = -8

The incorrect steps in the solution are;

The incorrect step in Mai's solution is the step; 7·x + 3 = 3(9)

The previous equation before the step 12·x + 3 = 3·(5·x + 9), can be expanded to get;

12·x + 3 = 15·x + 27

Therefore, Mai subtracted 7·x from 12·x to get 5·x rather than 15·x from 12·x to get (-3·x)

The incorrect step in Noah's solution is the step 27·x + 3 = 27

The previous equation before the step 12·x + 3 = 15·x + 27, indicates that collecting like terms, we get;

On the left hand side; 12·x - 15·x = -3·x

However Noah may have evaluated 12·x + 15·x = 27·x

Therefore, there terms 12·x and 15·x are added rather than subtracted in the step

The complete question found through search can be presented as follows;

Mai and Noah also solved the equation but some of their steps have errors. Find the incorrect step in each solution and explain why it is incorrect

Mai

14·x - 2·x + 3 = 3·(5·x + 9)

12·x + 3 = 3·(5·x + 9)

7·x + 3 = 3(9)

7·x + 3 = 27

7·x = 24

x = 24/7

Noah

14·x - 2·x + 3 = 3·(5·x + 9)

12·x + 3 = 15·x + 27

27·x + 3 = 27

27·x = 24

x = 24/27

User Mathachew
by
5.2k points